1997
DOI: 10.1021/np9605201
|View full text |Cite
|
Sign up to set email alerts
|

New Guaiane Metabolites from the Caribbean Gorgonian Coral, Pseudopterogorgia americana

Abstract: Six new sesquiterpenes having the guaiane skeleton were isolated from the hexane extract of the Caribbean gorgonian coral Pseudopterogorgia americana collected in Puerto Rico. Their structure assignments and relative stereochemistries were based on interpretation of spectroscopic data, molecular modeling studies, and comparisons with known compounds. Most of the new metabolites were found to be quite labile and decomposed slowly under normal spectral measurement conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…According to the DEPT spectrum of the cyclopentadiene substructure (three quaternary carbons and a methane for sp 2 carbons), the second isomer is probably furanoguaia-1,3-diene. [20] f Identified by NMR according to Blay et al [36] g Identified by NMR according to Rodriguez et al [32] h Percentages evaluated by combination of GC-FID and NMR. Comparing the relative ratio of both isomers in the 13 C-NMR spectrum of the EO and in the fractions of CC suggested that the furanoguaia-1,4-diene was partially isomerized in its 1,3 isomer during fractionation on CC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the DEPT spectrum of the cyclopentadiene substructure (three quaternary carbons and a methane for sp 2 carbons), the second isomer is probably furanoguaia-1,3-diene. [20] f Identified by NMR according to Blay et al [36] g Identified by NMR according to Rodriguez et al [32] h Percentages evaluated by combination of GC-FID and NMR. Comparing the relative ratio of both isomers in the 13 C-NMR spectrum of the EO and in the fractions of CC suggested that the furanoguaia-1,4-diene was partially isomerized in its 1,3 isomer during fractionation on CC.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 25, 45, 46 and 48 1bH,7aH,10bH-Guaia-4,11-diene, 25 Electron impact MS 70 eV, m/z (relative intensity): 204 (35), 189 (57), 161 (31), 147 (25), 133 (32), 119 (52), 105 (77), 95 (100), 91 (76), 79 (89), 77 (42), 67 (44), 55 (46), 41 (58) and 39 (34).Furanoguaia-1,4-diene, 45 and furanoguaia-1,3-diene, 46 1 H-and 13 C-NMR data, seeTable 2; EI-MS 70 eV, m/z (relative intensity): 214 (45), 199 (68), 128(16), 115(15), 109(16), 108 (100), 107(20), 106 (41), 105(18), 91 (43), 79(32), 77(35), 77(30), 69(15), 65(18) and 39(14).…”
mentioning
confidence: 99%
“…The structures of prototype lactones 222-226, which were trivially designated americanolides, were established by spectroscopic methods, mainly NMR and MS. 227 The molecular structure of methoxyamericanolide B (225), including relative stereochemistry, was later confirmed by single-crystal X-ray crystallography. 229,230 In all, 17 guaiane metabolites were isolated and purified, and their structures, including relative stereochemistry, deduced as 222-238 on the basis of interpretation of spectroscopic data in combination with X-ray crystallographic analyses. 229,230 In all, 17 guaiane metabolites were isolated and purified, and their structures, including relative stereochemistry, deduced as 222-238 on the basis of interpretation of spectroscopic data in combination with X-ray crystallographic analyses.…”
Section: Pseudopterogorgia Americana (Gmelin 1791)mentioning
confidence: 99%
“…Six new guaiane skeleton sesquiterpenes 358-363 were isolated from the hexane extract of the Caribbean gorgonian coral Psedopterogorgia americana collected in Puerto Rico. Although most metabolites were found to be labile and decomposed slowly under normal conditions, americanolide D 359 showed strong cytotoxicity against the human colon (KM-12) cancer cells and methoxyamericaolide A which is a derivative of methoxyamericanolide G 363, is a strong and selective in vivo inhibitor of MOLT-4 leukemia cells [122].…”
Section: Sesquiterpenes (Table 13)mentioning
confidence: 99%